URGENSI CIVIC EDUCATION DALAM MEMBANGUN BUDAYA DEMOKRASI MENUJU MASYARAKAT MADANI INDONESIA: SEBUAH PENDEKATAN FIQH SIYASAH - Muhammad Iqbal (JURIS (Jurnal Ilmiah Syariah), 2016)
In the current history of Indonesia, discussions concerning the implementation of democracy seem to be ups and downs. In general, it can be said that the implementation of democracy has not met the noble ideas of the 1945 Proclamation. Consequently, civilized society development as promoted by the second principle of Pancasila has not been completely realized. This article therefore aims at presenting a description of political journeys of Indonesian and a model of civic education in developing democracy in order to achieve the ideal civil society. This can realized prioritizing understanding towards people’s rights, educating people to be more critical toward current issues, and promoting open mindedness and accepting all the existing differences